In search of Alvar Aalto : a portuguese journey in 1957 - Duarte, João Miguel Couto, 1966- (2021)
James Joyce (1882-1941) begins his book "A Portrait of the Artist as a Young Man" (1916), the story of the coming-of-age of Stephen Dedalus, with an epigraph from Ovid’s Metamorphoses: "Et ignotas animum dimittit in artes" [1, p. 2]. This mysterious epigraph presents a processual scenario where the figure of Daedalus, in his role as maker and in his effort to escape, becomes a shadow that is constantly present. An idea imbibed in dynamic principles associated with what could potentially exist is not indifferent to this notion of process. That idea is argued by Fritz Senn with regard to the short quotation from Ovid (43BC-17AC): “[t]he emphasis is not so much on the achievement, artes […], for that remains doubtful always, but on the process. The prerequisites are not so much erudition, though that helps quite a bit, but curiosity and versatility.” [2, p. 127]